Kilo-scale droplet generation in three-dimensional monolithic elastomer device (3D MED). Issue 23 (2nd October 2015) - Jeong, Heon-Ho; Yelleswarapu, Venkata R.; Yadavali, Sagar; Issadore, David; Lee, Daeyeon
Abstract : Three dimensional monolithic elastomer device (3D MED) for kilo-scale droplet generation (1.5 L per hour) is developed using a double-sided imprinting technique. Abstract : Droplet-based microfluidics has led to transformational new approaches in diverse areas including materials synthesis and high-throughput biological assays. However, the translation of droplet microfluidics technology into commercial applications requires scale-up of droplet generation from the laboratory (<10 mL h −1 ) to the industrial (>1 L h −1 ) scale. To address this challenge, we develop a three-dimensional monolithic elastomer device (3D MED) for mass production of monodisperse emulsion droplets. Using double-sided imprinting, 3D microchannels are formed in a single elastomer piece that has 1000 parallel flow focusing generators ( k -FFGs). Compared to previous work that parallelizes droplet generation, the 3D MED eliminates the needs for alignment and bonding of multiple pieces and thus makes it possible to achieve the high flow rates and pressure necessary for the kilo-scale generation of droplets. Using this approach, we demonstrate mass production of water-in-oil (W/O) emulsion droplets at production rates as high as 1.5 L h −1 (>30 billion 45 μm diameter droplets per hour), with a coefficient of variation of droplet diameter of only 6.6%. Because of the simplicity, robustness, and manufacturability of our 3D MED architecture, it is well suited to bridge the gap between the continuously growing library of promising microfluidic technologies to generate microparticles that have been demonstrated in laboratory settings and their successful application in industry.